R&D and Innovation in Food Processing Firms in Transition Countries. (11th August 2016) - Ghazalian, Pascal L.; Fakih, Ali
Abstract: We examine the implications of the liberalised economic conditions associated with the economic transformations in the transition countries of Central and Eastern Europe (CEE) and Commonwealth of Independent States (CIS) for R&D and innovation in the food processing sector. We use a dataset derived from the World Bank's Business Environment and Enterprise Performance Surveys (BEEPS) database to examine the relationships between R&D/innovation activities in food processing firms in transition countries and (i) privatisation, (ii) foreign direct investment, (iii) trade activities, (iv) market competition pressure, and (v) economies of scale. The empirical analysis is implemented through: (i) a double‐hurdle model for R&D participation and expenditures, and (ii) a bivariate probit model for product and process innovation. We find that these economic transformations generally promote R&D/innovation activities in the food processing sector. Our results suggest that broadened and deepened economic liberalisation policies would improve the innovation performance of the food processing sector in transition countries, and would enhance competitiveness in domestic and foreign markets. They also indicate that innovation policies may need to be tailored to market and industrial characteristics of different transition regions.